Child Labor in Indonesia - Utama, Resa Surya; Handayani, Dwini (Jurnal Ekonomi Kuantitatif Terapan; 2020: Vol. 13, No. 1, Februari 2020 (pp. 1-210), 2020)
Children in employment will potentially lose their chances on education and threaten their human capital development. Labour market theory posited that their existence is in accordance to supply and demand of workforce. This study is making use of logistic regression on Susenas and Podes 2018 to examine the theory presumption. The results suggest that Micro Small Industry (IMK) presence and poverty status are playing roles in children's employment. In addition, head of household’s characteristics, such as their level of education and work status, also contribute significantly. Establishing social assistance programs is paramount in solving child labour issues in Indonesia.